Rhythmic Relating: Bidirectional Support for Social Timing in Autism Therapies - Daniel, Stuart; Wimpory, Dawn; Delafield-Butt, Jonathan T.; Malloch, Stephen; Holck, Ulla; Geretsegger, Monika; Tortora, Suzi; Osborne, Nigel; Schögler, Benjaman; Koch, Sabine; Elias-Masiques, Judit; Howorth, Marie-Claire; et al. (Frontiers in Psychology, 2022)
We propose Rhythmic Relating for autism: a system of supports for friends, therapists, parents, and educators; a system which aims to augment bidirectional communication and complement existing therapeutic approaches. We begin by summarizing the developmental significance of social timing and the social-motor-synchrony challenges observed in early autism. Meta-analyses conclude the early primacy of such challenges, yet cite the lack of focused therapies. We identify core relational parameters in support of social-motor-synchrony and systematize these using the communicative musicality constructs: pulse; quality; and narrative. Rhythmic Relating aims to augment the clarity, contiguity, and pulse-beat of spontaneous behavior by recruiting rhythmic supports (cues, accents, turbulence) and relatable vitality, facilitating the predictive flow and just-ahead-in-time planning needed for good-enough social timing. From here, we describe possibilities for playful therapeutic interaction, small-step co-regulation, and layered sensorimotor integration. Lastly, we include several clinical case examples demonstrating the use of Rhythmic Relating within four different therapeutic approaches (Dance Movement Therapy, Improvisational Music Therapy, Play Therapy, and Musical Interaction Therapy). These clinical case examples are introduced here and several more are included in [Please insert a note here + relevant link, to the online supplementary doc]. A suite of pilot intervention studies is proposed to assess the efficacy of combining Rhythmic Relating with different therapeutic approaches in playful work with individuals with autism. Further experimental hypotheses are outlined, designed to clarify the significance of certain key features of the Rhythmic Relating approach.